Emotional and cognitive responses to romantic breakups in adolescents and young adults: the role of rumination and coping mechanisms in life impact - Mancone, Stefania; Celia, Giovanna; Bellizzi, Fernando; Zanon, Alessandra; Diotaiuti, Pierluigi (Frontiers in Psychiatry, 2025)
BackgroundRomantic breakups can significantly impact the psychological well-being of young adults, affecting emotional, physical, and social domains. This study examines the roles of rumination and coping strategies in shaping adjustment to breakup-related distress, specifically focusing on Italian adolescents and young adults.MethodsA sample of 560 participants aged 17 to 22 who had recently experienced a romantic breakup completed questionnaires assessing rumination, coping strategies, and perceived impacts on life domains such as academic performance, family relationships, physical health, and emotional well-being. Correlation, regression, and mediation analyses were conducted to explore the relationships between rumination, coping strategies, and adjustment outcomes.ResultsRumination emerged as a significant predictor of negative outcomes in academic performance and physical health. Avoidance coping mediated the relationship between rumination and emotional well-being, suggesting that individuals who ruminate are more likely to adopt avoidance strategies, leading to greater emotional distress. Conversely, adaptive strategies like Positive Attitude and Problem Solving were associated with better adjustment, predicting improved academic performance and healthier family relationships.ConclusionsThe findings underscore the importance of addressing rumination and avoidance coping in interventions aimed at supporting young adults post-breakup. Encouraging adaptive coping strategies, such as Positive Attitude and Problem Solving, could enhance resilience and mitigate the negative effects of relationship dissolution. This study contributes to a better understanding of coping processes in a culturally specific context, highlighting potential avenues for fostering resilience in youth facing emotional challenges.